‘No Plastic Bag Day’ campaign in Selangor: effects on consumers’ attitudes and behaviours - Rajan, Shantakumari; Mohd Nasir, Nor Farrahanim; Mohamad Shaifuddin, Siti Norashikin; Azmi, Alia; Masngut, Mohd Izwan; Mohd Shahid, Nadiatul Syima; Suwandi, Nur Rohmah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
Excessive use of plastic grocery bags has led to a substantial accumulation of plastic waste, which, if not managed properly, contributes to environmental pollution. To address this issue, Selangor has launched the ‘No Plastic Bag Day’ (NPBD) campaign, which has been active for over a decade to reduce the use of plastic bags. This cross-sectional study aims to provide insight into how NPBD campaign in Selangor affects customer attitudes and behaviours. An online survey was conducted with 389 participants in Selangor using snowball sampling and distributed via social media. For data analysis, descriptive statistics and linear regression tests were conducted using SPSS version 28. Findings revealed that consumers in Selangor exhibit positive attitudes (mean score: 73% ± 19%) and moderately positive behaviours (mean score: 53% ± 17%) towards the use of plastic bags and the NPBD campaign. Statistical analysis revealed a significant association between consumers’ attitude and behaviour scores, as well as between gender and attitudes, and between gender and educational level with behaviours (p<0.05). Findings indicated a generally positive outcome to the implementation of the NPBD campaign; however, further research, such as longitudinal or intervention-based studies, is recommended to evaluate longterm behavioural changes and the sustained impact of the campaign. In terms of implementation, data indicate that sociodemographic factors should be considered when designing interventions to enhance the reach and impact of sustainable practices in Selangor.